Identification of Brucella spp. isolates and discrimination from the vaccine strain Rev.1 by MALDI-TOF mass spectrometry. (June 2020) - Christoforidou, Sofia; Kyritsi, Maria; Boukouvala, Evridiki; Ekateriniadou, Loukia; Zdragas, Antonios; Samouris, Georgios; Hadjichristodoulou, Christos
Abstract: Brucellosis' surveillance and control programs require robust laboratory techniques that can reliably identify and biotype Brucella strains and discriminate between vaccine and field infection. In the recent years, Matrix Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS) has revolutionized the routine identification of several microorganisms in clinical microbiology laboratories. Nevertheless, its application on Brucella spp. identification is limited since there are no reference spectra in the commercial databases, due to the microorganism's potential bioterrorist use. In this study, a custom MALDI-TOF MS reference library was constructed and its performance on identification at species level was evaluated using 75 Brucella spp. isolates. Furthermore, distinct peak biomarkers were detected for biovar assignment and discrimination from vaccine strain Rev.1. Analysis of mass peak profiles allowed Brucella accurate identification at genus and species level (100%) with no misidentifications. Despite the high intrageneric similarity, MALDI-TOF MS database succeeded in classifying at biovar level, 47 out of 62 B. melitensis bv. 3 isolates (75.81%), whereas all B. melitensis strains, except for one, were correctly discriminated from vaccine strain Rev.1. MALDI-TOF MS appeared to be a rapid, cost-effective and reliable method for the routine identification of brucellae which reduces time consumption in pathogen identification and could replace in the near future the current conventional and molecular techniques. Its ability to differentiate vaccine from field infection could facilitate brucellosis' monitoring systems contributing in the effective control of the disease. Highlights: Brucellosis is a zoonosis often misdiagnosed and underreported in endemic areas. MALDI-TOF is a promising tool for brucellosis routine identification and diagnosis. The assignment of B. melitensis biovars lies on peak biomarkers' determination. The method could help discriminate between field and vaccine infection.